Bilateral glymphatic dysfunction and its association with disease duration in unilateral temporal lobe epilepsy patients with hippocampal sclerosis - Xie, Fangfang; Zhou, Chunyao; Jin, Hong; Xing, Wu; Wang, Dongcui (Epilepsy & behavior, 2024)
•The bilateral glymphatic profile of unilateral TLE patients with histologically proved hippocampal sclerosis (HS) was evaluated by the DTI-ALPS method.•In comparison to HCs, the TLE patients with HS showed significantly reduced DTI-ALPS indices bilaterally, and the reduction was more pronounced ipsilaterally.•In TLE patients with HS, the ipsilateral DTI-ALPS index was found slightly lower than the contralateral but without evident statistical significance.•In TLE patients with HS, the ipsilateral DTI-ALPS index was significantly inversely correlated with disease duration. In this study, the diffusion tensor imaging along perivascular space analysis (DTI-ALPS) technique was utilized to evaluate the functional changes in the glymphatic system of the bilateral hemispheres in patients with unilateral temporal lobe epilepsy (TLE) accompanied by hippocampal sclerosis (HS). The aim was to gain insights into the alterations in the glymphatic system function in TLE patients. A total of 61 unilateral TLE patients with HS and 53 healthy controls (HCs) from the Department of Neurosurgery at Xiangya Hospital were included in the study. All subjects underwent DTI using the same 3 T MR Scanner, and the DTI-ALPS index was calculated. Differences in the DTI-ALPS index between TLE patients and HCs were evaluated, along with the correlation between the DTI-ALPS index of TLE and clinical features of epilepsy. These features included age, age of onset, seizure duration, and neuropsychological scores. Compared to the bilateral means of the HCs, both the ipsilateral and contralateral DTI-ALPS index of the TLE patients were significantly decreased (TLE ipsilateral 1.41 ± 0.172 vs. HC bilateral mean: 1.49 ± 0.116, p = 0.006; TLE contralateral: 1.42 ± 0.158 vs. HC bilateral mean: 1.49 ± 0.116, p = 0.015). The ipsilateral DTI-ALPS index in TLE patients showed a significant negative correlation with disease duration (r = -0.352, p = 0.005). The present study suggests the presence of bilateral dysfunctions in the glymphatic system and also highlight a laterality feature in these dysfunctions. Additionally, the study found a significant negative correlation between the ipsilateral DTI-ALPS index and disease duration, underscoring the significance of early effective interventions and indicating potential for the development of innovative treatments targeting the glymphatic system.